2020
DOI: 10.3390/ijms21155305
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility of Host Transcriptome Profiling as a Diagnostic Tool for Microbial Etiology in Childhood Cancer Patients with Febrile Neutropenia

Abstract: Infection is a common and serious complication of cancer treatment in children that often presents as febrile neutropenia (FN). Gene-expression profiling techniques can reveal transcriptional signatures that discriminate between viral, bacterial and asymptomatic infections in otherwise healthy children. Here, we examined whether gene-expression profiling was feasible in children with FN who were undergoing cancer treatment. The blood transcriptome of the children (n = 63) was investigated at time of FN diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 27 publications
0
21
1
Order By: Relevance
“…Notably, in the current study, only ~40% of the FN had a proven etiology, which is a limitation of our study. However, it also highlights the importance of improved methods for microbial detection in children with ALL as suggested by us previously [ 35 ].…”
Section: Discussionmentioning
confidence: 63%
“…Notably, in the current study, only ~40% of the FN had a proven etiology, which is a limitation of our study. However, it also highlights the importance of improved methods for microbial detection in children with ALL as suggested by us previously [ 35 ].…”
Section: Discussionmentioning
confidence: 63%
“…To our knowledge, this is the rst study to identify feature genes in OM development by WGCNA and machine learning. Some published studies suggested that the host blood transcriptional pro les play an essential role in diagnosing infectious diseases [18,[32][33][34]. It is worth noting that one previous study [11] divided samples into three comparison groups, including all of the S. aureus patients vs. Ctrl group (i.e., healthy people), OM patient vs. Ctrl group, and OM patients vs. non-OM patient following S. aureus infection.…”
Section: Discussionmentioning
confidence: 99%
“…By using a multi-data cohort approach including both adult and pediatric patients, and also animals in one of the studies, two research groups were able to identify a 7-and 4-script-Host RNA signature that discriminated viral from bacterial infection and viral from non-infective inflammation with high accuracy [75,76]. These gene expression-based diagnostic approaches are promising and have been proven superior to other biomarkers, such as white blood counts and PCT [63,64,78], but further evaluation in different patient cohorts is needed, especially since a recent publication could show that gene expression profiling was not feasible in children under treatment for cancer and presenting with febrile neutropenia [81].…”
Section: Pathogen-specific Signatures In Childrenmentioning
confidence: 99%